An Analysis of Science Activities in Pre-School Education Programmes in Northern Cyprus and Turkey / Kuzey Kıbrıs ve Türkiye Okul Öncesi Eğitim Programlarında Yer Alan Fen Etkinliklerinin Analizi - Kiraz, Aşkın; Sıddık, Hulin (Journal of History Culture and Art Research, 2018)
Abstract Pre-school science education is one of the most important educational processes that enables inquiry, problem-solving, exploring and commenting in children. With a qualified science education, children can develop their curiosity and appreciation for nature while becoming science literate. Furthermore, children who learn to transfer their knowledge of daily life also develop scientific process skills and problem-solving abilities. These competencies are acquired through pre-school education when the child actively participates in the process. The child solves and explains the complex activities surrounding him/her with the support of science activities he/she sees as a game in the science education process. Thus, it is recommended to gain an individual who has developed a sense of research and interpretation. In this study, the aim is to examine the Pre-School Education Program of the Ministry of National Education which is being taught in Turkish Republic of North Cyprus and Republic of Turkey with a specific focus on science activities. In the study, the activities in the program are examined in terms of number, subject, scope, achievement and applicability in accordance with qualitative research and document analysis. Additionally, alternative science activities have been proposed in parallel with the topics in the study. As a result, it has been determined that the number of science activities is kept low in both programs, the subjects which are important outcomes of contemporary life such as environment, animal, soil are not included in programs too much, and the activities are not able to respond to all of the determined achievements. Öz Okul öncesinde fen eğitimi; çocukta sorgulamayı, araştırmayı, problem çözmeyi, keşfetmeyi ve yorum geliştirmeyi sağlayan önemli eğitim süreçleri arasındadır. Nitelikli bir fen eğitimi ile çocuklar, fen okuryazarı olurken, doğaya karşı duydukları merak ve ilgilerini geliştirirler. Bu sırada bilgilerini günlük hayata transfer etmeyi öğrenenirler, bilimsel süreç becerilerini geliştirirler ve problem çözme davranışlarını artırırlar. Okul öncesi eğitimde bu yetkinliklerin kazandırılması, çocuğun aktif olarak sürece katılması ile olur. Çocuk, fen eğitimi sürecinde oyun olarak gördüğü fen etkinlikleri desteğiyle çevresindeki karmaşık olayları çözümler ve anlamlandırır. Böylece eğitim sürecinde araştırma ve yorumlama duygusu gelişmiş bir birey kazandırmak hedeflenir. Bu çalışmada Kuzey Kıbrıs Türk Cumhuriyeti ve Türkiye Cumhuriyeti’nde okutulmakta olan KKTC MEB Okul Öncesi Eğitim Programının ve TC MEB Okul Öncesi Eğitim Programının fen etkinlikleri kapsamında incelenmesi amaçlanmıştır. Çalışmada, her iki programda yer alan etkinlikler nitel araştırmaya ve doküman analizine uygun olarak sayı, konu, kazanım, uygulanabilirlik gibi alt birimler altında incelenmiştir. Ayrıca çalışmada konular paralelinde alternatif fen etkinlikleri önerilmiştir. Sonuç olarak her iki programda da fen etkinliklerinin sayısının az tutulduğu, güncel hayatın önemli getirisi olan çevre, hayvan, toprak gibi konulara çok fazla yer verilmediği ve etkinliklerin belirlenen kazanımların hepsine cevap veremediği saptanmıştır.